Implementasi Program Keluarga Harapan Di Dinas Sosial Kabupaten Donggala - Haeruddin Haeruddin (Jurnal ADMINISTRATOR, 2021)
The purpose of this study was to find out the implementation of the Family Hope Program (PKH) Policy at the Social Office of Donggala Regency. The research method uses a qualitative descriptive approach. Determination of informants is done purposively. Collecting data using observation, interviews and documentation. Data analysis used the Miles and Huberman interactive model approach, namely data collection, condensation, display and data verification. The results of the study indicate that: (1) Aspects of communication, PKH implementers in Donggala Regency have built communication between the parties, providing relevant information, but socialization is not routinely carried out to the parties, especially cross-agency officials who need this information. (2) resources (Resouces), the availability of resources in the implementation of the Family Hope Program in Donggala Regency is supported by the availability of PKH human resources (HR) recruited under the conditions of academic standards and experience set by the Ministry of Social Affairs, then strengthened by training and technical guidance and has met the ratio of 1 (one) social assistant accompanying 250KPM, (3) the implementer (disposition), in terms of loyalty, commitment and honesty of the implementer in the implementation of the family hope program has been running in accordance with the code of ethics set by the institution, based on values ​​and polite attitude, integrity and professionalism. (4) the bureaucratic structure, the implementation of PKH activities has been carried out based on the source of the Operational Procedure (SOP), as well as fragmentation in the form of distribution of authority, the hierarchy has run quite synergistically between the government units involved